Montenegro After the Crisis : Towards a Smaller and More Efficient Government - World Bank (Washington, DC, 2013)
Recognizing the important progress with structural reforms so far, on October 12, 2011, the European Commission recommended the opening of formal membership negotiations for Montenegro. Further, in December 2011, Montenegro was granted the membership in the World Trade Organization (WTO), and in June 2012, the country is expected to open the first chapters in membership negotiations with the European Union (EU). These are major milestones on Montenegro's road to the European Union provides a broad external and institutional context, and the destination, for its ongoing reform efforts in a complex international economic environment. In this context, Montenegro needs to continue to strive to improve its policy environment and manage its public expenditures efficiently and improve the quality of public services for all its citizens. Building on the past analytical reports and ongoing economic policy dialogue, this report aims to provide new analysis, ideas, and policy advice to Montenegro's authorities on how to accelerate its public expenditure reforms with the view to reducing cost, improving quality, and increasing public service delivery.